We're Here! We're Sphere! Get Used To It!: Anti-Fatness at the Theatre Academy - Kronholm, Ida (Taideyliopiston Teatterikorkeakoulu, 2025)
This is a thesis inspired by autotheory and stand-point theory, in which I present experiences lived by myself and four other fat students at the Uniarts Helsinki Theatre academy. Drawing on literature from the field of fat studies as a part of gender studies, it explores how anti-fat attitudes have shown themselves in the interactions we have had with individuals and structures at the academy and how we as individuals who have been shaped by anti-fat bias and abuse outside of the Theatre academy cope within it. Additionally, the thesis compares statements from the Uniarts Helsinki vision statement and Safer spaces guidelines and argues that for fat people at the academy these guidelines and goals are not upheld nor reached. Fat students at the academy face bias and abuse, they limit themselves personally and artistically and are actively limited artistically by teachers and peers, they receive movement training of lesser quality than their thin peers and they are not supported in becoming self-confident fat artists when they leave the academy. The method used is interviews in the form of small talk between author and interviewee. The interviewees and their quotes have been anonymized, and the quotes have been scrambled so as to form a mass of experiences rather than shaping rosters of individual experiences for each interviewee. The interview materials have been categorized through close reading, following the themes arisen in the interviews. The categories are as follows: 1. Getting in – experiences from entrance exams 2. Opting out – experiences of self-censorship and exclusion 3. Fitting in – experiences from the costume department 4. Staying fat – temporality of identity and the pressure to shrink 5. Getting out – how has the school prepared us for the field? 6. Stigma, slurs and surviving This thesis came about due to my own hurt as a fat person studying at the Theatre academy, and my own experiences of not being heard or supported when expressing this hurt. I chose to place myself as an active part of the thesis för several reasons: to include my own experiences in order to have more voices in the mix; to assert myself in my fat identity; to place myself and fat narrative as part of the stand-point theory canon; to practice the principle I inherited from my mentor Suzanne Osten to always as a director be ready to answer any question I put to an actor or colleague.
Keywords: anti-fatness; pro-thin bias; Students and staff of the Uniarts Helsinki theatre academy; kokemukset; teatteritaide; identiteetti; minäkuva; teatterikorkeakoulut; safer space principles; discrimination; self-esteem; lihavuus; roolitus; fi=ohjaus|sv=regi|en=Directing|